Adsorbent for separating parachlorotoluene and o-chlorotoluene and preparation method thereof
By using chromium nitrate and 2-amino phenyl-phenylic acid preparing, separate adsorption particles, and inlaid them in inhalation carriers such as foam nickel, solve the problem of insufficient selection of chlorophyllopine and adjacent chloropenene in existing technologies. Achieve efficient separation effects.
Patent Information
- Application Number
- CN202411884099.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-01-21
AI Technical Summary
The existing molecular sieve adsorption and separation process is inadequate in the separation of parachlorotoluene and o-chlorotoluene, resulting in low separation efficiency and difficult subsequent treatment.
Chromium nitrate and 2-aminoterephthalic acid are used as raw materials to prepare separation adsorption particles, and their surface characteristics and adsorption performance are enhanced through activation treatment. The separation adsorption particles are embedded on adsorption carriers such as nickel foam to improve the mass transfer rate and selective adsorption capacity.
The effective separation of chlorophyllin and adjacent chloropenene, improved separation efficiency and selectivity, and reducing the difficulty of subsequent treatment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of separation of para-chlorotoluene and ortho-chlorotoluene, and in particular to an adsorbent for separation of para-chlorotoluene and ortho-chlorotoluene and a preparation method thereof. Background Art
[0002] Chlorotoluene has three isomers, namely o-chlorotoluene (OCT), m-chlorotoluene and p-chlorotoluene (PCT), among which OCT is widely used as an intermediate in the pesticide, pharmaceutical and dye industries. OCT mainly uses toluene as raw material. The reaction product obtained by catalytic chlorination contains both OCT and PCT. The mass fraction of OCT is about 50%. Even if a highly selective chlorinated KL molecular sieve catalyst is used, the mass fraction of OCT in the chlorinated liquid obtained after chlorination can still reach about 30%. Since the atmospheric boiling points of OCT and PCT differ by only 3°C, the relative volatility of the two calculated based on the saturated vapor pressure at normal temperature and pressure is only 1.17, which shows that the separation of OCT and PCT is relatively difficult.
[0003] In the existing method of separating o-chlorotoluene and p-chlorotoluene, a molecular sieve adsorption separation process is usually used for separation and purification of isomer mixtures. However, in the process of separating p-chlorotoluene and o-chlorotoluene, the molecular sieve has insufficient selectivity for p-chlorotoluene and o-chlorotoluene, and the molecular sieve may have little difference in adsorption capacity for them. This insufficient selectivity will reduce the efficiency of the separation process and increase the difficulty of subsequent treatment. Summary of the invention Based on the technical problems existing in the above-mentioned prior art, the present invention provides an adsorbent for separating para-chlorotoluene and o-chlorotoluene and a preparation method thereof.
[0004] In the first aspect, the present application provides an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene, using the following technical solution: An adsorbent for separating para-chlorotoluene and ortho-chlorotoluene comprises an adsorption carrier and separation adsorption particles coated on the surface of the adsorption carrier, wherein the separation adsorption particles are made by the following technical scheme: Chromium nitrate and 2-aminoterephthalic acid are stirred and mixed, and sodium hydroxide solution is added, and the mixture is stirred and mixed, and the mixture is placed in a reaction kettle, and the temperature is increased and kept to react; The mixture was allowed to stand and cool to room temperature, the reactants were collected and centrifuged, and the lower precipitate was collected and vacuum dried to prepare separation adsorption particles.
[0005] Through the above technical scheme, the technical scheme of the present application prepares separation adsorption particles by using chromium nitrate and 2-aminoterephthalic acid as raw materials. Since meta-xylene and o-xylene are stacked in pairs inside the separation adsorption particles during the separation adsorption process, the π-π interaction between the molecules is stronger, and the meta-position hydrophobicity is stronger, so para-xylene, o-xylene, and meta-xylene are passed through the above adsorbent material in turn, thereby achieving effective separation of para-chlorotoluene and o-chlorotoluene.
[0006] Furthermore, the separation and adsorption of particles further comprises an activation process, and the activation process comprises the following steps: The separation adsorption particles are mixed with ethanol and placed in a reaction device, heated and hydrothermally treated, left to cool to room temperature, centrifuged and dried, so as to prepare the activated separation adsorption particles.
[0007] Through the above technical solution, the technical solution of the present application can effectively enhance the surface characteristics of the particles by mixing the separation adsorption particles with ethanol and performing hydrothermal treatment under elevated temperature conditions, thereby improving their adsorption performance. The present application can promote the structural reorganization and functionalization of the separation adsorption particles through activation treatment, and improve the selective adsorption capacity of para-chlorotoluene and ortho-chlorotoluene. The adsorption particles after such treatment can better interact with the target molecules and improve the separation efficiency.
[0008] Furthermore, the temperature of the insulation reaction is 140-160° C., and the insulation reaction time is 24 hours.
[0009] Furthermore, the hydrothermal treatment is a hydrothermal reaction at 100-110° C. for 24 hours.
[0010] In a second aspect, the present application provides a method for preparing an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene, comprising the following technical solutions: A method for preparing an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene, comprising the following preparation steps: Polyethylene glycol, soluble starch, silica sol and deionized water are mixed and stirred, dispersed by ball milling, and a mixed slurry is collected; Taking the mixed slurry and stirring it with the separation adsorption particles, and collecting the dispersed coating liquid by ultrasonic dispersion; The adsorption carrier is dip-coated with the dispersed coating liquid on its surface by the dipping and pulling method. After the dipping and pulling is completed, it is placed in a muffle furnace after drying, heated and calcined to prepare an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene.
[0011] Through the above technical scheme, the technical scheme of the present application loads separation adsorption particles on an adsorption carrier, and improves the defects of poor adsorption performance and low mass transfer rate of single separation adsorption particles by embedding the separation adsorption particles on the adsorption carrier. The mass transfer rate of the separation adsorption particles is increased by the adsorption carrier, thereby further improving the effect of the separation adsorption particles in separating para-chlorotoluene and ortho-chlorotoluene.
[0012] Furthermore, the adsorption carrier includes at least one of foamed metal and zeolite molecular sieve.
[0013] Furthermore, the foam metal is foam nickel, and the porosity of the foam nickel is 94-96%.
[0014] Through the above technical solutions, the technical solution of this application optimizes the selection of adsorption carriers and further optimizes their porosity. By increasing the porosity, it helps to improve the fluidity and diffusivity of the fluid, thereby enhancing the efficiency of the adsorption separation process. The high porosity of nickel foam not only increases the specific surface area of the adsorbent, but also enhances its ability to capture fluids during use, thereby improving the separation effect of para-chlorotoluene and ortho-chlorotoluene, and is suitable for the field of efficient separation and purification.
[0015] Furthermore, a pre-processing step is included, wherein the pre-processing step adopts the following technical solution: The nickel foam material is respectively placed in acetone, anhydrous ethanol and deionized water for ultrasonic washing, and then placed in a sodium hydroxide solution for alkaline washing, washed and dried to complete the pretreatment step.
[0016] Through the above technical solution, the technical solution of the present application performs ultrasonic washing and alkaline washing on the nickel foam material to remove impurities and pollutants on the surface, and the alkaline washing helps to increase the active sites on the surface of the material and improve the efficiency of the subsequent adsorption process. This pretreatment method significantly improves the surface properties of the nickel foam, so that it exhibits better performance in the process of adsorbing para-chlorotoluene and ortho-chlorotoluene, ensuring the effectiveness and reliability of the separation agent.
[0017] In summary, this application has the following beneficial effects: First, the technical solution of the present application uses chromium nitrate and 2-aminoterephthalic acid as raw materials to prepare separation adsorption particles. During the separation adsorption process, meta-xylene and o-xylene are stacked in pairs inside the separation adsorption particles, the π-π interaction between molecules is stronger, and the hydrophobicity of the meta position is stronger. Therefore, para-xylene, o-xylene, and meta-xylene are passed through the above-mentioned adsorbent material in turn, thereby achieving effective separation of para-chlorotoluene and o-chlorotoluene.
[0018] Second, the technical solution of the present application loads separation adsorption particles on an adsorption carrier. By embedding the separation adsorption particles on the adsorption carrier, the defects of poor adsorption performance and low mass transfer rate of single separation adsorption particles are improved. The mass transfer rate of the separation adsorption particles is increased by the adsorption carrier, thereby further improving the effect of the separation adsorption particles in separating para-chlorotoluene and ortho-chlorotoluene.
[0019] Third, the technical solution of this application optimizes the selection of adsorption carriers and further optimizes their porosity. By increasing the porosity, it helps to improve the fluidity and diffusivity of the fluid, thereby enhancing the efficiency of the adsorption separation process. The high porosity of nickel foam not only increases the specific surface area of the adsorbent, but also enhances its ability to capture fluids during use, thereby improving the separation effect of parachlorotoluene and orthochlorotoluene, and is suitable for the field of efficient separation and purification. DETAILED DESCRIPTION
[0020] The present application is further described in detail below with reference to the embodiments.
[0021] In the examples of the present application, the raw materials and instruments used are as follows, but not limited thereto. Raw materials not otherwise specified are of analytical grade.
[0022] Preparation Example 1 Separation of adsorbed particles 1 Take 300g of chromium nitrate and 130g of 2-aminoterephthalic acid, stir and mix, add 500g of 1% by mass sodium hydroxide solution, stir and mix, place in a reactor, heat to 140°C, and keep warm for 24h; The mixture was allowed to stand and cool to room temperature, the reactants were collected and centrifuged at 3500 r / min for separation, the lower precipitate was collected and vacuum dried at 60° C. for 8 h, and the separation adsorption particles 1 were prepared.
[0023] Preparation Example 2 Separation of adsorbed particles 2 Take 325g of chromium nitrate and 140g of 2-aminoterephthalic acid, stir and mix, add 550g of 1% sodium hydroxide solution, stir and mix, place in a reactor, heat to 150°C, and keep the temperature for 24h; The mixture was allowed to stand and cool to room temperature, the reactants were collected and centrifuged at 3500 r / min for separation, the lower precipitate was collected and vacuum dried at 60° C. for 8 h, and the separation adsorption particles 2 were prepared.
[0024] Preparation Example 3 Separation of adsorbed particles 3 Take 350g of chromium nitrate and 150g of 2-aminoterephthalic acid, stir and mix, add 600g of 1% sodium hydroxide solution, stir and mix, place in a reactor, heat to 140-160°C, and keep warm for 24h; The mixture was allowed to stand and cool to room temperature, the reactants were collected and centrifuged at 3500 r / min, the lower precipitate was collected, and vacuum dried at 60° C. for 8 h to prepare separation adsorption particles 3.
[0025] Preparation Example 4 Separation of adsorbed particles 4 Take 325g of chromium nitrate and 140g of 2-aminoterephthalic acid, stir and mix, add 550g of 1% sodium hydroxide solution, stir and mix, place in a reactor, heat to 150°C, and keep the temperature for 24h; The reaction mixture was cooled to room temperature, and the reaction mixture was collected and centrifuged at 3500 r / min. After collecting the lower precipitate, it was vacuum dried at 60°C for 8 hours, and then mixed with 800 g of anhydrous ethanol and placed in a reaction device, heated to 100-110°C for hydrothermal reaction for 24 hours, cooled to room temperature, centrifuged at 3500 r / min, and vacuum dried at 60°C for 8 hours to prepare separation adsorption particles 4. Preparation Example 5 Pretreated adsorption carrier A foamed nickel material with a porosity of 94-96% was placed in acetone, anhydrous ethanol, and deionized water for ultrasonic washing for 5 minutes, then placed in a 0.1 mol / L sodium hydroxide solution for alkaline washing for 20 minutes, rinsed with deionized water for 3-5 times, and then dried at 50°C for 8 hours to prepare a pretreated adsorption carrier.
[0026] Example 1 An adsorbent for separating para-chlorotoluene and ortho-chlorotoluene comprises an adsorption carrier and separation adsorption particles coated on the surface of the adsorption carrier.
[0027] A method for preparing an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene, comprising the following preparation steps: Take 20g of polyethylene glycol, 3g of soluble starch, 15g of silica sol with a solid content of 10% and 500g of deionized water, stir and mix, ball mill and disperse at room temperature for 30min, and collect the mixed slurry; Take 200 g of the mixed slurry and stir and mix it with 3 g of separation adsorption particles 1, and ultrasonically disperse it at 300 W for 15 min to collect the dispersed coating liquid; The foamed nickel material with a porosity of 94% is dip-coated with a dispersed coating liquid on its surface by an immersion pulling method, and the pulling speed is set to 20 mm / min. After the immersion pulling is completed, it is placed in a 60°C oven for drying for 3 hours, and then placed in a 450-550°C heat preservation and roasting treatment for 2 hours to prepare an adsorbent for separation of para-chlorotoluene and ortho-chlorotoluene.
[0028] Example 2 An adsorbent for separating para-chlorotoluene and ortho-chlorotoluene comprises an adsorption carrier and separation adsorption particles coated on the surface of the adsorption carrier.
[0029] A method for preparing an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene, comprising the following preparation steps: Take 35g of polyethylene glycol, 5g of soluble starch, 15g of silica sol with a solid content of 10% and 650g of deionized water, stir and mix, ball-mill and disperse for 30min at room temperature, and collect the mixed slurry; Take 250g of the mixed slurry and stir it with 4g of separation adsorption particles 2, and disperse it ultrasonically at 300W for 15min, and collect the dispersed coating liquid; The foamed nickel material with a porosity of 95% is dip-coated with a dispersed coating liquid on its surface by an immersion pulling method, and the pulling speed is set to 20 mm / min. After the immersion pulling is completed, it is placed in a 60°C oven for drying for 3 hours, and then placed at 500°C for calcination for 2 hours to prepare an adsorbent for the separation of para-chlorotoluene and ortho-chlorotoluene.
[0030] Example 3 An adsorbent for separating para-chlorotoluene and ortho-chlorotoluene comprises an adsorption carrier and separation adsorption particles coated on the surface of the adsorption carrier.
[0031] A method for preparing an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene, comprising the following preparation steps: Take 50g of polyethylene glycol, 8g of soluble starch, 15g of silica sol with a solid content of 10% and 800g of deionized water, stir and mix, ball mill and disperse at room temperature for 30min, and collect the mixed slurry; Take 300g of the mixed slurry and stir it with 5g of separation adsorption particles 3, disperse it ultrasonically at 300W for 15min, and collect the dispersed coating liquid; The foamed nickel material with a porosity of 95% is coated with a dispersed coating liquid on its surface by an immersion pulling method, and the pulling speed is set to 20 mm / min. After the immersion pulling is completed, it is placed in a 60°C oven for drying for 3 hours, and then placed at 550°C for calcination for 2 hours to prepare an adsorbent for separation of para-chlorotoluene and ortho-chlorotoluene.
[0032] Example 4 An adsorbent for separating para-chlorotoluene and ortho-chlorotoluene comprises an adsorption carrier and separation adsorption particles coated on the surface of the adsorption carrier.
[0033] A method for preparing an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene, comprising the following preparation steps: Take 35g of polyethylene glycol, 5g of soluble starch, 15g of silica sol with a solid content of 10% and 650g of deionized water, stir and mix, ball-mill and disperse for 30min at room temperature, and collect the mixed slurry; Take 250g of the mixed slurry and stir it with 4g of separation adsorption particles 4, disperse it ultrasonically at 300W for 15min, and collect the dispersed coating liquid; The foamed nickel material with a porosity of 95% is dip-coated with a dispersed coating liquid on its surface by an immersion pulling method, and the pulling speed is set to 20 mm / min. After the immersion pulling is completed, it is placed in a 60°C oven for drying for 3 hours, and then placed at 500°C for calcination for 2 hours to prepare an adsorbent for the separation of para-chlorotoluene and ortho-chlorotoluene.
[0034] Example 5 An adsorbent for separating para-chlorotoluene and ortho-chlorotoluene comprises an adsorption carrier and separation adsorption particles coated on the surface of the adsorption carrier.
[0035] A method for preparing an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene, comprising the following preparation steps: Take 35g of polyethylene glycol, 5g of soluble starch, 15g of silica sol with a solid content of 10% and 650g of deionized water, stir and mix, ball-mill and disperse for 30min at room temperature, and collect the mixed slurry; Take 250g of the mixed slurry and stir it with 4g of separation adsorption particles 4, disperse it ultrasonically at 300W for 15min, and collect the dispersed coating liquid; The pretreated adsorption carrier is dip-coated with the dispersed coating liquid on its surface by the immersion pulling method, and the pulling speed is set to 20 mm / min. After the immersion pulling is completed, it is placed in a 60°C oven for drying for 3 hours, and then placed at 500°C for calcination for 2 hours to prepare the adsorbent for separation of para-chlorotoluene and ortho-chlorotoluene.
[0036] Performance Testing The adsorbent for separating para-chlorotoluene and ortho-chlorotoluene prepared in Example 1-5 was tested. Specifically, its separation performance was tested. A finished ortho-chlorotoluene product having an ortho-chlorotoluene mass fraction of 99.75% and a para-chlorotoluene mass fraction of 0.25% was tested. The adsorbent for separating para-chlorotoluene and ortho-chlorotoluene prepared in Example 1-5 was placed in the finished ortho-chlorotoluene product, stirred at room temperature for 2 hours, filtered, and sampled for gas chromatography analysis. The results are shown in Table 1 below: Table 1 Performance test table
[0037] From the above examples 1-5, combined with the test results in Table 1, it can be found that: The technical solution of the present application uses chromium nitrate and 2-aminoterephthalic acid as raw materials to prepare separation adsorption particles. During the separation adsorption process, meta-xylene and o-xylene are stacked in pairs inside the separation adsorption particles, the π-π interaction between molecules is stronger, and the hydrophobicity of the meta position is stronger. Therefore, para-xylene, o-xylene, and meta-xylene are passed through the above-mentioned adsorbent material in sequence, thereby achieving effective separation of para-chlorotoluene and o-chlorotoluene.
[0038] Secondly, by comparing Examples 1-3 with Example 4, it is further illustrated that the present application loads separation adsorption particles on an adsorption carrier, and improves the defects of poor adsorption performance and low mass transfer rate of a single separation adsorption particle by embedding the separation adsorption particle on the adsorption carrier. The mass transfer rate of the separation adsorption particle is increased by the adsorption carrier, thereby further improving the effect of the separation adsorption particle in separating para-chlorotoluene and ortho-chlorotoluene.
[0039] Comparing Example 4 with Example 5, it is shown that the technical solution of the present application removes impurities and pollutants on the surface by ultrasonic washing and alkaline washing of the nickel foam material, and the alkaline washing helps to increase the active sites on the surface of the material and improve the efficiency of the subsequent adsorption process. This pretreatment method significantly improves the surface properties of the nickel foam, so that it exhibits better performance in the process of adsorbing para-chlorotoluene and ortho-chlorotoluene, and ensures the effectiveness and reliability of the separation agent.
[0040] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
[0041] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.
[0042] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0043] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
Claims
1. An adsorbent for separating para-chlorotoluene and ortho-chlorotoluene, characterized in that: It includes an adsorption carrier and separation adsorption particles coated on the surface of the adsorption carrier, and the separation adsorption particles are made by the following technical scheme: Chromium nitrate and 2-aminoterephthalic acid are stirred and mixed, and sodium hydroxide solution is added, and the mixture is stirred and mixed, and the mixture is placed in a reaction kettle, and the temperature is increased and kept to react; The mixture was allowed to stand and cool to room temperature, the reactants were collected and centrifuged, and the lower precipitate was collected and vacuum dried to prepare separation adsorption particles.
2. The adsorbent for separation of para-chlorotoluene and ortho-chlorotoluene according to claim 1, characterized in that: The separation and adsorption of particles further comprises an activation process, wherein the activation process comprises the following steps: The separation adsorption particles are mixed with ethanol and placed in a reaction device, heated and hydrothermally treated, left to cool to room temperature, centrifuged and dried, so as to prepare the activated separation adsorption particles.
3. The adsorbent for separation of para-chlorotoluene and ortho-chlorotoluene according to claim 1, characterized in that: The temperature of the insulation reaction is 140-160° C., and the insulation reaction time is 24 hours.
4. The adsorbent for separation of para-chlorotoluene and ortho-chlorotoluene according to claim 2, characterized in that: The hydrothermal treatment is a hydrothermal reaction at 100-110° C. for 24 hours.
5. The method for preparing an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene according to any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: Polyethylene glycol, soluble starch, silica sol and deionized water are mixed and stirred, dispersed by ball milling, and a mixed slurry is collected; Taking the mixed slurry and mixing it with the separation adsorption particles, and ultrasonically dispersing and collecting to obtain the dispersed coating liquid; The adsorption carrier is dip-coated with the dispersed coating liquid on its surface by the dipping and pulling method. After the dipping and pulling is completed, it is placed in a muffle furnace after drying, heated and calcined to prepare an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene.
6. The method for preparing an adsorbent for separation of para-chlorotoluene and ortho-chlorotoluene according to claim 5, wherein the adsorption carrier comprises at least one of foamed metal and zeolite molecular sieve.
7. The method for preparing an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene according to claim 6, characterized in that: The foam metal is foam nickel, and the porosity of the foam nickel is 94-96%.
8. The method for preparing an adsorbent for separating para-chlorotoluene and ortho-chlorotoluene according to claim 6, characterized in that: The pretreatment step is also included, and the pretreatment step adopts the following technical scheme: The nickel foam material is respectively placed in acetone, anhydrous ethanol and deionized water for ultrasonic washing, and then placed in a sodium hydroxide solution for alkaline washing. After washing and drying, the pretreatment step is completed.